ПРОГРАМНЕ ЗАБЕЗПЕЧЕННЯ РОЗРАХУНКУ І ВИБОРУ УСТАВОК ПАРАМЕТРІВ СПРАЦЬОВУВАННЯ МОДУЛЯ ФАЗОВОГО СЕЛЕКТОРА З СЕКТОРОМ НАВАНТАЖЕННЯ - Колесникова, Н.Ф.; Козлова, О.І.; Литвинова , О.А. (Інститут електродинаміки Національної академії наук України, 2019)
Presents the results of work on the creation of software to ensure settlement and the choice of the settings of the Phase Selector Settings with Load Sector.The purpose of this work was the need to supplement the IEDKK10-RW automated calculations complex of emergency modes and setpoints of MPs of the ABB REL6 ** devices for overhead lines and AT in complex electrical networks up to 10,000 nodes developed and implemented into commercial operation at NEK Ukrenergo and its Regional Dispatch Rooms Centers of Ukraine with software for performing automated calculations and selecting settings for the phase selector and the load sector. The work was carried out due to the need for correct and reliable selection of the damaged phase during short circuits throughout the length of the line that is protected in all modes and to eliminate false alarms with large power flows in the terminal on long heavily loaded lines to ensure efficient operation of single phase automatic reclosing on overhead lines. References 1, figures 7.